Research and Development for Poverty Reduction of the Community in the Place of Civilisation with the Philosophy of the Sufficiency Economy - Insawan, Nattakit (Ratchaphruek Journal, 2015)
This research aimed to study the community’s context in the place of civilisation in Nonsung district in Nakhon Ratchasima province for setting up an effective plan for poverty solving based on the Philosophy of Sufficiency Economy. This research indicated that the target population was very poor and the community’s problems were unfortunate circumstance in agricultural land, natural disaster; flood and drought, popularity and attitude for unsuitable careers, supported by government; a lack of budget, solving without sincerity, and misunderstanding of community’s context, unfortunate rules/regulations for developing and absolute poverty solving, and lack of knowledge; a leader of community, a local authority, and an administrator lacked understanding of poverty solving in a local area. In this research, the researchers suggested 4 strategies of the effective plan for poverty solving based on the sufficiency economy as follows; Management of Community’s Natural Resources and Environment, Community’s Business Support for Poverty Solving, Development of Local Administration for Poverty Solving, and Increases of the Poor’s Efficiency and Potential. As a result, the community has a plan to poverty reduction at the community level as a system, participate in resolving and encourage the use of local resources effectively.